Analysis of Medical Records Personnel Needs Based on Service Workload Using the ABK-Kes Method - Ervina Damayanti; Wisoedhanie Widi Anugrahanti; Bhre Diansyah Dinda Khalifatulloh; Nita Dwi Nur Aini; Moh Maulana (Jurnal Kesehatan Cendikia Jenius, 2026)
An imbalance between workload and the number of medical record officers may reduce service quality and increase work-related fatigue, making workload-based staffing analysis essential. This study aimed to analyze the staffing needs of medical record officers based on workload using the Health Workload Analysis Method (ABK-Kes) at Ciptomulyo Public Health Center. A quantitative descriptive design with an observational analytic approach was employed, involving all medical record officers totaling two respondents through total sampling. Data were collected in May 2025 using observation, interviews, and document review, and analyzed using the ABK-Kes method, including calculations of Available Working Time, time norms, Standard Workload, Support Task Factor, and Standard Support Task. The results showed that the workload of medical record officers was relatively high, with an average of 130 patient visits per day, a Support Task Factor of 24%, and a Standard Support Task value of 1.31. The ABK-Kes analysis indicated that the ideal number of medical record officers required was three, revealing a shortage of one officer. In conclusion, additional medical record staff are necessary to balance workload, improve service quality, and reduce the risk of work-related fatigue, and the findings are recommended as a basis for human resource planning at public health centers.